Pelatihan Kader Kesehatan dalam Perawatan Kulit Lansia - Maria Prieska Putri Panglipur Ati; Oda Debora (Yayasan Inspirasi El Burhani, 2023)
Introduction: Elderly is an age group that is at risk of experiencing disturbances in body tissues, one of which is skin tissue. The structure of the elderly's skin changes, including dry skin, wrinkles, and itching. The Sukoharjo Village, which is under the auspices of the Bareng Health Center, only has 16 health cadres and functions as an informal caregiver to care for the elderly indirectly. Informal caregivers do not have a formal educational background in terms of skin care, causing problems related to their competence. Objective: The purpose of this service was to improve the ability and skills of health cadres in elderly skin care. Method: This public service was conducted by lectured, discussion, and demonstration. The approach taken is to provide education about long-term care and skin care as well as training in elderly skin care through bathing the elderly. Result: The activity partners were 16 health cadres in RW 1 and 2, Sukoharjo Village. The results of the activity showed an increase in knowledge of 40% of cadres who had good knowledge, while 73% of health cadres had good skills in providing skin care to the elderly. Conclusion: Health cadres who are given training on elderly skin care are expected to be able to transfer the knowledge that has been given to caregivers who are in RW 1 and RW 2 for the sake of improving the quality of life of the elderly.